ANALISIS PROFIL FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN BATANG KAYU SMIDRA (Acronychia pedunculata (L.) Miq - Fajeriyati, Nurul; Perdana, Farid; Musthapa, Iqbal (Jurnal Insan Farmasi Indonesia, 2024)
The Rutaceae family is a family known to have antioxidant activity, one of the species included in the Rutaceae family is Acronychia pedunculata (L.) Miq commonly known as smidra. Plant parts of Acronychia pedunculata (L.) Miq such as roots, stems, leaves and fruit are used for traditional medicine for diarrhea, cough, asthma, wounds, boils, itchy skin, scales, pain and rheumatism and can be used as a fever reducer and can be used for the treatment of digestive tract disorders such as ulcers and intestinal infections. This study aims to determine the phytochemical profile and antioxidant activity of Acronychia pedunculata (L.) Miq smidra wood. In this study, the phytochemical profile analysis test was carried out, including the test of simplisia characteristics, monitoring the spectrum pattern using FTIR and chromatogram pattern using KLT and antioxidant activity test using DPPH method. The results showed that Acronychia pedunculata (L.) Miq smidra wood contains acetophenone derivative compounds with at least 5 compound components. Antioxidant activity test with DPPH method produces IC50 of 9.68 ppm which is included in the category of very strong antioxidants.